Minocycline Treatment Reduces Mass and Force Output From Fast-Twitch Mouse Muscles and Inhibits Myosin Production in C2C12 Myotubes - Kiriaev, Leonit; Perry, Ben D.; Mahns, David A.; Shortland, Peter J.; Redwan, Asma; Morley, John W.; Head, Stewart I. (Frontiers in Physiology, 2021)
Minocycline, a tetracycline-class of antibiotic, has been tested with mixed effectiveness on neuromuscular disorders such as amyotrophic lateral sclerosis, autoimmune neuritis and muscular dystrophy. The independent effect of minocycline on skeletal muscle force production and signalling remain poorly understood. Our aim here is to investigate the effects of minocycline on muscle mass, force production, myosin heavy chain abundance and protein synthesis. Mice were injected with minocycline (40 mg/kg i.p.) daily for 5 days and sacrificed at day six. Fast-twitch EDL, TA muscles and slow-twitch soleus muscles were dissected out, the TA muscle was snap-frozen and the remaining muscles were attached to force transducer whilst maintained in an organ bath. In C2C12 myotubes, minocycline was applied to the media at a final concentration of 10 μg/mL for 48 h. In minocycline treated mice absolute maximal force was lower in fast-twitch EDL while in slow-twitch soleus there was an increase in the time to peak and relaxation of the twitch. There was no effect of minocycline treatment on the other contractile parameters measured in isolated fast- and slow-twitch muscles. In C2C12 cultured cells, minocycline treatment significantly reduced both myosin heavy chain content and protein synthesis without visible changes to myotube morphology. In the TA muscle there was no significant changes in myosin heavy chain content. These results indicate that high dose minocycline treatment can cause a reduction in maximal isometric force production and mass in fast-twitch EDL and impair protein synthesis during myogenesis in C2C12 cultured cells. These findings have important implications for future studies investigating the efficacy of minocycline treatment in neuromuscular or other muscle-atrophy inducing conditions.